2022
DOI: 10.1111/nmo.14410
|View full text |Cite
|
Sign up to set email alerts
|

Gastroenterology Trainees’ Attitudes and Knowledge towards Patients with Disorders of Gut‐Brain Interaction

Abstract: Disorders of gut-brain interaction (DGBI), also known as functional gastrointestinal (GI) disorders, affect about 40% of the global population. 1 DGBIs occur as a result of complex interactions between biological, psychological, and social factors. 2 The treatment paradigm for DGBIs has advanced to encompass pharmacologic approaches (e.g., neuromodulators targeting central modulation of pain processing pathways) as well as non-pharmacologic modalities such as brain-gut behavior therapies (BGBT) and dietary mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(24 citation statements)
references
References 20 publications
3
21
0
Order By: Relevance
“… 16 , 17 , 18 A recent survey of gastroenterology trainees within the United States reported that (a) ∼50% have sometimes witnessed dismissive attitudes from their attendings and peers towards patients with DGBI, (b) ∼21% felt frustrated or burnt out when seeing patients with DGBI, (c) ∼40% preferred not to see a patient with DGBI, and (d) ∼27% felt uncomfortable titrating neuromodulators. 19 A lack of familiarity can lead to incorrect diagnosis and management, and perhaps a perception that these disorders lack importance, culminating in suboptimal care. In fact, general practitioners and non‐expert gastroenterologists are more likely to experience difficulties in confidently diagnosing common DGBI such as irritable bowel syndrome than they are inflammatory bowel disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 16 , 17 , 18 A recent survey of gastroenterology trainees within the United States reported that (a) ∼50% have sometimes witnessed dismissive attitudes from their attendings and peers towards patients with DGBI, (b) ∼21% felt frustrated or burnt out when seeing patients with DGBI, (c) ∼40% preferred not to see a patient with DGBI, and (d) ∼27% felt uncomfortable titrating neuromodulators. 19 A lack of familiarity can lead to incorrect diagnosis and management, and perhaps a perception that these disorders lack importance, culminating in suboptimal care. In fact, general practitioners and non‐expert gastroenterologists are more likely to experience difficulties in confidently diagnosing common DGBI such as irritable bowel syndrome than they are inflammatory bowel disease.…”
Section: Discussionmentioning
confidence: 99%
“…These concerns have also been echoed by gastroenterology trainees across Australia, Europe, and the United States, and are likely to resonate across the globe 16–18 . A recent survey of gastroenterology trainees within the United States reported that (a) ∼50% have sometimes witnessed dismissive attitudes from their attendings and peers towards patients with DGBI, (b) ∼21% felt frustrated or burnt out when seeing patients with DGBI, (c) ∼40% preferred not to see a patient with DGBI, and (d) ∼27% felt uncomfortable titrating neuromodulators 19 . A lack of familiarity can lead to incorrect diagnosis and management, and perhaps a perception that these disorders lack importance, culminating in suboptimal care.…”
Section: Discussionmentioning
confidence: 99%
“…This could be facilitated by an increased number of gastroenterology junior clinical fellowships with exposure to procedures, a diverse range of clinics and ward-based care. This would allow procedural experience to be gained, as well as exposure to subspecialties with greater elements of patient centred care such as neurogastroenterology, which has recently been highlighted as a significant training gap for postgraduate doctors 21. Importantly, such opportunities would allow doctors to form pivotal mentor–mentee relationships which may further attract applicants, and be especially beneficial for female clinicians, while also contributing to interest and retention of male staff 22–25.…”
Section: Discussionmentioning
confidence: 99%
“…35 Among US gastroenterology trainees in their final year of training, 27.1% reported feeling "not comfortable at all" titrating neuromodulators. 36 Best practice advice suggests providers familiarize themselves with dosing, side effects, and targets of a few select neuromodulators. 8 Refusal of neuromodulator therapy by patients is another factor limiting usage with 39% of gastroenterologists reporting that at least 20% of their patients refused a neuromodulator prescription.…”
Section: Centr Al Neuromodul Ator Smentioning
confidence: 99%
“…For example, 69.1% of gastroenterologists reported referral to a psychiatrist for their patients with IBS 35 and only 31.6% of trainees were "comfortable" or "very comfortable" with referral to gastropsychologists for their patients with DGBI. 36 However, the increasing availability of brain-gut behavior health digital therapeutics provides adjunctive tools for patients with DGBI to treat their symptoms. 48 Management of chronic GI pain in DGBI is complex and often re-…”
Section: Non -Pharmacolog Ic Manag Ementmentioning
confidence: 99%